Analisis Pelaksanaan Tanggungjawab Sosial Perusahaan (CSR) PT. Toba Pulp Lestari, Tbk di Kabupaten Toba Samosir Ditinjau Dari UU PT. No. 40 Tahun 2007 - Ebenezer Simanullang; Bismar Nasution; Muhammad Yamin; Mahmul Siregar (USU LAW JOURNAL, 2019)
Abstract. In Indonesia, the implementation of corporate social responsibility (CSR) was regulated in Law Number 40 of 2007 about Limited Company which contained in Chapter V Article 74, the further provision about Social and Environmental Responsibility were regulated with Governments Regulation No. 47 of 2012 in Article 4.  The fund which channeled through corporate social responsibility was in the amout of 1% of net sales (Net Sales). The CSR implementation constraint which experienced by PT. Toba Pulp Lestari, Tbk in an internal company manner was in the implementation of social investment (development) program. Likewise, the external constraint which experienced by PT Toba Pulp Lestari, Tbk among others, were the existence of management institution of CD / CSR fund company formed by the Regional Government which previously formed and the result of report after audited "Not Stating Opinion" (Disclaimer). The existence of partly districts which were late in submitting the program and even there are some who never submit the program and the formation of a new district, which result in change in the calculation of the company's CD / CSR fund allocation budget. Uneven the distribution of CD / CSR corporate funds to the society in Toba Samosir District in general. Keywords: corporate social responsibility, PT Toba Pulp Lestari, Tbk